2019
DOI: 10.1002/ijop.12621
|View full text |Cite
|
Sign up to set email alerts
|

Psychological maladjustment mediates the link between remembrances of parental rejection in childhood and loneliness in adulthood: A cross‐cultural comparative study

Abstract: Drawing stimulus from interpersonal acceptance‐rejection theory, this multicultural study examined relations between men's versus women's remembrances of maternal and paternal acceptance‐rejection in childhood and their current level of loneliness, as mediated by adults' self‐reported psychological maladjustment. Adults (N = 899) from five nations (Iraq, Italy, the Netherlands, Pakistan, and the United States) responded to the Adult version of the Parental Acceptance‐Rejection Questionnaire‐short form for moth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 31 publications
2
13
0
1
Order By: Relevance
“…The more the individuals feel distressed by loneliness, the higher their reported psychological maladjustment. This result is consistent with the previous literature (Heinrich and Gullone, 2006;Richardson et al, 2017;Menec et al, 2020;Rohner et al, 2020;Wang et al, 2020) highlighting the link between loneliness, psychosocial difficulties, and mental health and is consistent with the IPARTheory, postulating that the perception of unsatisfactory and rejecting interpersonal relationships are associated with psychological maladjustment (Rohner, 2019).…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…The more the individuals feel distressed by loneliness, the higher their reported psychological maladjustment. This result is consistent with the previous literature (Heinrich and Gullone, 2006;Richardson et al, 2017;Menec et al, 2020;Rohner et al, 2020;Wang et al, 2020) highlighting the link between loneliness, psychosocial difficulties, and mental health and is consistent with the IPARTheory, postulating that the perception of unsatisfactory and rejecting interpersonal relationships are associated with psychological maladjustment (Rohner, 2019).…”
Section: Discussionsupporting
confidence: 92%
“…Results of Study 2 showed, as expected, that the perception of loneliness in adults is strongly associated with the general psychological adjustment and that this effect is observed beyond age and gender differences (Rohner et al, 2020). These results allowed further verification of the validity of the IPARLS scores (concurrent validity) and confirmed that the IPARLS is a valid tool for monitoring loneliness distress among the adult age groups.…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations